Maternal Mortality Decline in the Kassena-Nankana District of Northern Ghana - Mills, S.; Williams, J. E.; Wak, G.; Hodgson, A. (2012)
OBJECTIVE: In the absence of an adequate vital registration system in Ghana, the Navrongo demographic surveillance system (NDSS) established in 1993 presents a viable alternative to monitor, in a poor rural district, the UN Millennium Development Goal on maternal health (MDG) of reducing maternal mortality by 75% between 1990 and 2015. METHODS: Of the 518 women aged 12-49 years identified in the NDSS database to have died in the Kassena-Nankana district in the period January 2002-December 2004, spouses or family members completed verbal autopsy interviews for 516 female deaths. RESULT: Of the 516 female deaths, 45 were identified as maternal deaths. 71% of the maternal deaths were attributed to direct maternal causes while 29% were due to indirect maternal causes. Abortion-related deaths were the most frequent cause of maternal deaths. The maternal mortality ratio for the period 2002-2004 was 373 maternal deaths per 100,000 live births indicating a 40% reduction of maternal mortality from the 1995-1996 level of 637 maternal deaths per 100,000 live births. However, the health-facility based maternal mortality ratio in the district (which excludes maternal deaths outside health facilities) was 141 maternal deaths per 100,000 live births for the period 2002-2004. CONCLUSION: This district may be on track to achieve the MDG on maternal health. Ultimately, strengthening vital registration systems to provide timely information to policymakers should supersede the other methods of measuring maternal mortality.